2002
DOI: 10.2519/jospt.2002.32.8.399
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Antagonist/Agonist Isokinetic Work Ratios of Shoulder Rotators in Men Who Play Badminton

Abstract: Study Design: Normative descriptive study. Objectives: Exploring the isokinetic work ratios of eccentric antagonist/concentric agonist shoulder rotators in the late cocking and deceleration phases of a forehand overhead smash in badminton players. Comparing the work ratios between dominant and nondominant shoulders. Background: The strength of shoulder muscles for badminton players has been studied but there is little information on the work output of these muscles for a specific range of movement. Methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 19 publications
0
51
0
4
Order By: Relevance
“…For the U/Es, this method has been proposed, to better evaluate the relationship between shoulder rotators. [16][17][18] Ng et al 19 and more recently Yildiz et al 18 used this eccentricconcentric approach to report torque ratios over an angular section (terminal range) where the antagonist muscles played a decelerator role (eccentric contractions). For these authors, this method is well adapted for investigating shoulder dynamic stability, especially among athletes performing overhead tasks (that is, throwing).…”
Section: Limits Of Agonist-antagonist Peak Torque Ratiosmentioning
confidence: 99%
“…For the U/Es, this method has been proposed, to better evaluate the relationship between shoulder rotators. [16][17][18] Ng et al 19 and more recently Yildiz et al 18 used this eccentricconcentric approach to report torque ratios over an angular section (terminal range) where the antagonist muscles played a decelerator role (eccentric contractions). For these authors, this method is well adapted for investigating shoulder dynamic stability, especially among athletes performing overhead tasks (that is, throwing).…”
Section: Limits Of Agonist-antagonist Peak Torque Ratiosmentioning
confidence: 99%
“…Greater repetitive use of the preferred arm in throwing actions in recreational and sporting activities may explain our asymmetry results [2,21]. However, previous studies have used a variety of different speeds in order to provide sport specific information about strength imbalance and injury risk in the shoulder rotators [3,4,9]. The use of a single velocity to describe angle specific strength is a limitation of our study.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, a few studies have opted to use 5°, 10°, 15° or end of ROM angle specific torque (AST) intervals for a more accurate estimation of unilateral dynamic muscle balance of the knee or shoulder joints [1,3,4,[6][7][8][9]. Dehail et al [7] demonstrated there was a significant progressive decline of flexion/extension and abduction/adduction AST strength ratios as the shoulder progressed to flexion and abduction, respectively.…”
Section: Contextmentioning
confidence: 99%
See 2 more Smart Citations